PENGARUH LINGKUNGAN BELAJAR TERHADAP MINAT BELAJAR SISWA SMK NEGERI 1 KOTA JAMBI - Yolanda Yolanda; Yanto; Freddi Sarman (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the phenomenon of low student learning interest at SMK Negeri 1 Jambi City. It can be seen from students who are not active in asking questions, body gestures that show no enthusiasm in learning, and there are some students who are lazy to do assignments. One of the factors suspected to influence it is the learning environment. Therefore, this study aims to determine the effect of the learning environment on the learning interest of students at SMK Negeri 1 Jambi City. The type of research used is quantitative research, with an ex post facto approach. With a population of 1282 students. The sample determination used stratified random sampling using the Slovin formula resulting in 93 students. Data collection techniques were carried out through observation, interviews, and Likert Scale questionnaires. Data analysis used data descriptions. And simple regression. The results of this study indicate that the learning environment variable is in the moderate category (82.8%), and the learning interest variable is also in the moderate category (76.34%). From the results of the simple regression analysis, a sig value of 0.000 <0.05 was obtained so that Ho was rejected and Ha was accepted. The analysis also showed that the learning environment had a 27.4% influence on students' learning interest, with other factors contributing 74%. Therefore, it can be concluded that the better the learning environment, the better the students' learning interest.